2021
DOI: 10.1021/acs.biomac.1c00353
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Electrospun Biopapers of Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) Derived from Cheese Whey with Varying 3-Hydroxyvalerate Contents

Abstract: In the present study, three different newly developed copolymers of poly(3-hydroxybutyrate- co -3-hydroxyvalerate) (PHBV) with 20, 40, and 60 mol % contents in 3-hydroxyvalerate (3HV) were produced by the biotechnological process of mixed microbial cultures (MMCs) using cheese whey (CW), a by-product from the dairy industry, as feedstock. The CW-derived PHBV copolyesters were first purified and then processed by solution electrospinning, yielding fibers of approximately 2 μm in cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 91 publications
2
19
0
Order By: Relevance
“…Shorter chains need less time for crystallization compared to longer chains which results in reduction of T c [ 49 ]. A T c value ranging from 41 to 82 °C for CHCl 3 extracted PHBV with 3HV contents of (20–60%) have been reported [ 50 ]. Another study had shown that PHBV (16.6% HV) extracted with NaClO and CHCl 3 had a T c value of 109 °C [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Shorter chains need less time for crystallization compared to longer chains which results in reduction of T c [ 49 ]. A T c value ranging from 41 to 82 °C for CHCl 3 extracted PHBV with 3HV contents of (20–60%) have been reported [ 50 ]. Another study had shown that PHBV (16.6% HV) extracted with NaClO and CHCl 3 had a T c value of 109 °C [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the conventional extraction/purification procedure adopted for obtaining pPHBV led to the recovery of a copolymer with a slightly lower ratio of HV. The HV content impacts the thermal and mechanical properties of the stored polymer and, in turn, its final application, as widely reported in the literature ( Melendez-Rodriguez et al, 2021 ).…”
Section: Discussionmentioning
confidence: 75%
“…The higher selectivity for odd-carbon VFA strategy can be of use in applications as, for example, the production of bioplastics as polyhydroxyalkanoates (PHA). PHA are bio-sourced biodegradable polyesters that can be produced biologically using VFA as substrate and that require a balanced mixture of odd-and even-carbon VFA to have properties that allow them to effectively substitute current oil-based polymers (Duque et al, 2014;Melendez-Rodriguez et al, 2021). If the VFA mixture obtained in the base case would be used for the synthesis, the obtained PHA would instead have much poorer mechanical properties, limiting the use for common applications such as packaging films (Cunha et al, 2016).…”
Section: Experimental Validation Of Second-round In Silico Experimentsmentioning
confidence: 99%